Estudios críticos sobre la violencia social, el compromiso político-ciudadano y la veracidad histórica en Noticia de un secuestro (1996) - Delgado Del Aguila, Jesús Miguel (2019)
News of a Kidnapping (1996), a journalistic novel by the Nobel Prize for Literature Gabriel Garcia Marquez, has allowed hermeneutical works to be carried out according to Cultural Studies, since its content covers historical periods in Colombia, Sociology, Criminology and politics: all linked to the writer's literary prose. On this occasion, what I represent are three aspects of research that have been developed based on the study of this work, which are the intentional manifestation of social violence in Colombia, the constitution of political-citizen commitment and authorial fidelity the historical exhibition in the same novel. The purpose of the confrontation and the intertextual dialogue with literary criticism is to establish a hermeneutical panorama with respect to what was determined in News of a kidnapping (1996).